Improvement of dense hydroxyapatite from natural bone with TiO2 powder - Sri Asliza, Mat Amin; Mohd Zaheruddin, Kasmuin; Siti Sarah, Ibrahim (Universiti Putra Malaysia (UPM), 2011)
Organized by Universiti Putra Malaysia (UPM), 10th - 12th December 2007 at Impiana Cherating Hotel at Pahang, Malaysia.